Salient Findings on Host Range, Resistance Screening, and Molecular Studies on Sterility Mosaic Disease of Pigeonpea Induced by Pigeonpea sterility mosaic viruses (PPSMV-I and PPSMV-II) - Sayiprathap, B. R.; Patibanda, A. K.; Prasanna Kumari, V.; Jayalalitha, K.; Ramappa, H. K.; Rajeswari, E.; Karthiba, L.; Saratbabu, K.; Sharma, Mamta; Sudini, H. K. (Frontiers in Microbiology, 2022)
Two distinct emaraviruses, Pigeonpea sterility mosaic virus-I (PPSMV-I) and Pigeonpea sterility mosaic virus-II (PPSMV-II) were found to be associated with sterility mosaic disease (SMD) of pigeonpea (Cajanus cajan (L.) Millisp.). Host-range of both these viruses and their vector is narrow, confined to N. benthamiana identified through mechanical transmission, and to Phaseolus vulgaris cvs. Top crop, Kintoki, and Bountiful (F: Fabaceae) through mite transmission. A weed host Chrozophora rottleri (F: Euphorbiaceae) was also infected and tested positive for both the viruses in RT-PCR. Among the wild Cajanus species tested C. platycarpus accessions 15661, 15668, and 15671 and C. scarabaeoides accessions 15683, 15686, and 15922 were infected by both the viruses and mite vector suggesting possibile sources of SMD inoculum. Though accession 15666 of C. platycarpus, 15696 of C. scarabaeoides, and 15639 of C. lancedatus were infected by both the viruses, no mite infestation was observed on them. Phylogenetic analysis of nucleotide sequences of RNA-1 and RNA-2 of PPSMV-I and PPSMV-II isolates in southern-India revealed significant divergence especially PPSMV-II is closely related to Fig mosaic virus (FMV) than PPSMV-I. In multi-location testing of pigeonpea genotypes for their broad-based resistance to SMD for two consecutive years, genotypes ICPL-16086 and ICPL-16087 were showed resistance reaction (<10 % incidence) in all three locations studied. Overall, the present study gives a clear idea about the host-range to PPSMV-I and PPSMV-II, their molecular relationship, and sources of resistance. This information is critical for the development of reliable diagnostic tools and improved disease management strategies.